2013
DOI: 10.1017/s204579601300067x
|View full text |Cite
|
Sign up to set email alerts
|

Cost drivers of inpatient mental health care: a systematic review

Abstract: Aims. New reimbursement schemes for inpatient mental health care are imminent in the UK and Germany. The shared intention is to reflect cost differences between patients in reimbursement rates. This requires understanding of patient characteristics that influence hospital resource use. The aim of this review was to show which associations between mental health care per diem hospital costs and patient characteristics are supported by current evidence. Methods. A systematic review of the literature published bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 26 publications
2
20
0
1
Order By: Relevance
“…While most of these characteristics have a consistent directional effect across sectors, older age is associated with higher costs in primary care but lower costs in specialised mental healthcare, suggesting a cross-sectoral shift in the cost burden over a patient's lifetime. Age and diagnostic category were also strong predictors of cost in Wolff et al [23], albeit the studies included in that review did not include only SMI patients and focused only on inpatient care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of these characteristics have a consistent directional effect across sectors, older age is associated with higher costs in primary care but lower costs in specialised mental healthcare, suggesting a cross-sectoral shift in the cost burden over a patient's lifetime. Age and diagnostic category were also strong predictors of cost in Wolff et al [23], albeit the studies included in that review did not include only SMI patients and focused only on inpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…Cost estimation studies tend to use a gross-costing methodology that often reflects reimbursement amounts, whereas micro-costing methods involve the enumeration of all resources consumed by a patient. A systematic review by Wolff et al [23] examining the association between mental healthcare hospital costs and patient characteristics considered costing approaches in mental healthcare more broadly, not just for SMI. It found that studies differed in their estimation of resource use and valuation.…”
Section: Background/rationalementioning
confidence: 99%
“…The Diagnosis Related Groups (314) system is widely used in acute general hospitals, but a consensus was reached over three decades ago that the system was inadequate for describing resource use in psychiatry (315). A number of studies pointed to the potential to use per-diem based case-mix systems that estimate costs of care per day of stay, rather than episode-based systems that attempt to predict length of stay (316)(317)(318).…”
Section: Resource Allocationmentioning
confidence: 99%
“…A number of studies pointed to the potential to use per-diem based case-mix systems that estimate costs of care per day of stay, rather than episode-based systems that attempt to predict length of stay (316)(317)(318). Most research of this type in mental health has been in hospital settings with only modest progress in community mental health services (319). In addition, although better than episode-based models, the ability to explain variance in resource use in psychiatry is lower than in more homogeneous care settings such as nursing homes (320).…”
Section: Resource Allocationmentioning
confidence: 99%
“…Inadäquat niedrige Krankenhausvergütung führt zu Fehlanreizen und damit zu volkswirtschaftlich ineffizienter Gesundheitsversorgung [15]. Stationäre Leistungserbringer würden dazu gedrängt, Kosten zulasten der Behandlungsqualität zu senken, die Verweildauer aus finanziellen Grün-den unter das medizinisch Notwendige zu verkürzen oder die Behandlung kostenintensiver Patienten gänz-lich zu vermeiden [3,6,13].…”
unclassified